Locating the agency of marginalized people: nomadic and post-nomadic service populations in Rajasthan, India - Motzafi-Haller, P (Anthropological Society of Oxford, 2012)
Using both ethnographic and survey data, this article explores the complex ways in which camp-dwellers on the margins of settled communities in Rajasthan, India, have interacted with state agents, services and systems of knowledge in a manner that articulates their limited but nonetheless significant agency. I explore three arenas through which the state's presence is felt in the lives of these marginalized people: access to land, to health services and to public schooling. I argue that marginalized people are not merely the victims of centrist powers but exhibit a resourcefulness and flexibility that redefines group boundaries and the impact of state policies on their lives.